Structure and interaction with phospholipids of a prokaryotic lipoxygenase from Pseudomonas aeruginosa. Issue 12 (28th August 2013) - Garreta, Albert; Val‐Moraes, Silvana P.; García‐Fernández, Queralt; Busquets, Montserrat; Juan, Carlos; Oliver, Antonio; Ortiz, Antonio; Gaffney, Betty J.; Fita, Ignacio; Manresa, Àngels; Carpena, Xavi
Abstract : Lipoxygenases (LOXs), which are essential in eukaryotes, have no confirmed function in prokaryotes that are devoid of polyunsaturated fatty acids. The structure of a secretable LOX from Pseudomonas aeruginosa ( Pa _LOX), the first available from a prokaryote, presents significant differences with respect to eukaryotic LOXs, including a cluster of helices acting as a lid to the active center. The mobility of the lid and the structural variability of the N‐terminal region of Pa _LOX was confirmed by comparing 2 crystal forms. The binding pocket contains a phosphatidylethanolamine phospholipid with branches of 18 ( sn ‐1) and 14/16 ( sn ‐2) carbon atoms in length. Carbon atoms from the sn‐1 chain approach the catalytic iron in a manner that sheds light on how the enzymatic reaction might proceed. The findings in these studies suggest that Pa _LOX has the capacity to extract and modify unsaturated phospholipids from eukaryotic membranes, allowing this LOX to play a role in the interaction of P. aeruginosa with host cells.—Garreta, A., Val‐Moraes, S. P., García‐Fernández, Q., Montserrat Busquets, C. J., Oliver, A., Ortiz, A., Gaffney, B. J., Fita, I., Manresa, A., Carpena, X., Structure and interaction with phospholipids of a prokaryotic lipoxygenase from Pseudomonas aeruginosa . FASEB J. 27, 4811‐4821 (2013). www.fasebj.org